Safety and feasibility of a novel multilectrode array catheter in mapping atrial and ventricular arrhythmias with high density: results from the multi-center OPTIMUM study. (19th May 2022) - Vijgen, J; Rackauskas, G; Dilling-Boer, D; Sarkozy, A; Ciconte, G; Vicedomini, GG; Pappone, C
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): This study was funded by Biosense Webster, Inc. Background/Introduction: The novel multielectrode array mapping catheter includes 48 electrodes symmetrically distributed across and along 6 splines (Picture), with an additional unipolar reference electrode to reduce far-field signals built in at the tip of the irrigation lumen. Preclinical studies demonstrated its ability to provide high density and high resolution mapping in complex substrates, but its usability and safety in patients with atrial or ventricular arrhythmias have not been investigated. Purpose: To assess the safety and mapping performance of the catheter with the electroanatomical navigation system for mapping in the atria and ventricle in patients with a variety of complex arrhythmias. Methods: The OPTIMUM study was a prospective, single arm study conducted at 3 European sites. Patients with scar-related atrial tachycardia (AT), PAF and persistent AF (PsAF), ventricular tachycardia (VT), or premature ventricular complexes (PVC) underwent pre-ablation mapping with the study catheter, and subsequent ablation according to institutional standard of care practice; the follow up period was 7 days. The primary safety endpoint was the incidence of device-related serious adverse events (SAE) within 7 days following the procedure. The primary effectiveness endpoint was the completion of protocol-required fast activation and electro anatomical pre-ablation mapping without resort to non-study mapping catheter(s), including fast anatomical mapping, mapping of substrate or any area of interest, and identification of conduction channel(s), gap(s) and critical isthmuses. General procedural characteristics as well as physician feedback (7-point Likert scale: 1 = poor and 7 = excellent) on various aspects of deployment, signal quality, and learning curve were also evaluated. Results: Thirty-one patients (mean age: 59.8±14 years, 71.0% male) were enrolled and treated (9 scar-related AT, 12 PAF, and 1 PsAF, 6 VT, and 3 PVC). There was no (0/31) SAE reported, and the primary effectiveness endpoint was achieved in all subjects (31/31). Almost all operators rated highly (≥ 5) on noise reduction in bipolar maps (30/31) and short learning curve (27/31). Bipolar signals and catheter maneuverability were rated highly favorable (≥5) in the left and right atria and met-expectation-and-above (≥4) in the left and right ventricles. Conclusion(s): The first-in-human clinical data demonstrate the safety and effectiveness of the novel microelectrode array mapping catheter to efficiently map various atrial and ventricular complex arrhythmias with good signal quality. Physicians indicated high satisfaction with the learning curve, catheter maneuverability, tissue characterization in all cardiac chambers.